Botanical Monography in the Anthropocene. (May 2021) - Grace, Olwen M.; Pérez-Escobar, Oscar A.; Lucas, Eve J.; Vorontsova, Maria S.; Lewis, Gwilym P.; Walker, Barnaby E.; Lohmann, Lúcia G.; Knapp, Sandra; Wilkie, Peter; Sarkinen, Tiina; Darbyshire, Iain; Lughadha, Eimear Nic; et al.
Abstract : Unprecedented changes in the Earth's biota are prompting urgent efforts to describe and conserve plant diversity. For centuries, botanical monographs — comprehensive systematic treatments of a family or genus — have been the gold standard for disseminating scientific information to accelerate research. The lack of a monograph compounds the risk that undiscovered species become extinct before they can be studied and conserved. Progress towards estimating the Tree of Life and digital information resources now bring even the most ambitious monographs within reach. Here, we recommend best practices to complete monographs urgently, especially for tropical plant groups under imminent threat or with expected socioeconomic benefits. We also highlight the renewed relevance and potential impact of monographies for the understanding, sustainable use, and conservation of biodiversity. Highlights: Botanical monographs have been the gold standard for communicating comprehensive systematic information about plants for over 300 years. Monographs catalyse species discovery, biodiversity documentation and conservation, and facilitate downstream research on wild and cultivated plant species. Increased availability of DNA sequence data and digitised resources now provide powerful resources for a new phase of collaborative efforts in monography, focussed on tackling the largest, most threatened, ecologically important, and economically valuable plant groups in an efficient manner.